Synthetic beta-solenoid proteins with the fragment-free computational design of a beta-hairpin extension - MacDonald,JT; Kabasakal,BV; Godding,D; Kraatz,S; Henderson,L; Barber,J; Freemont,PS; Murray,JW (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The ability to design and construct structures with atomic level precisionis one of the key goals of nanotechnology. Proteins offer anattractive target for atomic design, as they can be synthesized chemicallyor biologically, and can self-assemble. However the generalizedprotein folding and design problem is unsolved. One approach tosimplifying the problem is to use a repetitive protein as a scaffold.Repeat proteins are intrinsically modular, and their folding and structuresare better understood than large globular domains. Here, wehave developed a new class of synthetic repeat protein, based onthe pentapeptide repeat family of beta-solenoid proteins. We haveconstructed length variants of the basic scaffold, and computationallydesigned de novo loops projecting from the scaffold core. Theexperimentally solved 3.56 A resolution crystal structure of one designedloop matches closely the designed hairpin structure, showingthe computational design of a backbone extension onto a syntheticprotein core without the use of backbone fragments from knownstructures. Two other loop designs were not clearly resolved in thecrystal structures and one loop appeared to be in an incorrect conformation.We have also shown that the repeat unit can accommodatewhole domain insertions by inserting a domain into one of the designedloops.